HbA1C dan Profil Lipid sebagai Prediktor Komplikasi Penyakit Jantung pada Pasien Diabetes Mellitus (Journal of Telenursing (JOTING), 2024)
This study aims to analyze the relationship between HbA1C and lipid profiles consisting of total cholesterol, triglycerides, HDL-C, and LDL-C as predictors of heart disease complications in patients with type 2 diabetes. The method used is observational analytic with a cross-sectional design. The results showed that the average HbA1c level was 9.01%; the average Lipid Profile levels were total cholesterol: 240.98 mg/dL, triglycerides: 170.08 mg/dL, HDL-C: 43.86 mg/dL and LDL-C: 161.56 mg/dL. The results of the Spearman correlation test showed a relationship between HbA1C and lipid profiles (total cholesterol, triglycerides, HDL, and LDL) in patients with type 2 diabetes at H. Abdul Manap Regional Hospital, Jambi City. The conclusion of the study is that type 2 DM patients have poor glycemic control (average HbA1C levels of 9.01%, with dyslipidemia (total cholesterol, triglycerides, and LDL-C increased and low HDL-C), a relationship was found between HbA1C and lipid profiles. Keywords: Diabetes Mellitus, Hba1c, Lipid Profile, Heart Disease